2012
DOI: 10.1523/jneurosci.5198-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Cue Fronto-Occipital Alpha Phase and Distributed Cortical Oscillations Predict Failures of Cognitive Control

Abstract: Cognitive control is required for correct performance on antisaccade tasks, including the ability to inhibit an externally driven ocular motor repsonse (a saccade to a peripheral stimulus) in favor of an internally driven ocular motor goal (a saccade directed away from a peripheral stimulus). Healthy humans occasionally produce errors during antisaccade tasks, but the mechanisms associated with such failures of cognitive control are uncertain. Most research on cognitive control failures focuses on post-stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 56 publications
0
47
0
1
Order By: Relevance
“…A transcranial magnetic stimulation (TMS) study also found that when we used single-pulse TMS to interfere with the right DLPFC during the preparatory period, participants' AS performances suffered (Nyffeler et al, 2007). One study further found that patients with damage in the right VLPFC made more AS errors compared with patients with left VLPFC lesions (Hodgson et al, 2007). Given that no spatial information was present during the preparatory period, we found bilateral alpha-band modulation in the FEF during the preparatory period in preparation for inhibiting saccades to both hemifields (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A transcranial magnetic stimulation (TMS) study also found that when we used single-pulse TMS to interfere with the right DLPFC during the preparatory period, participants' AS performances suffered (Nyffeler et al, 2007). One study further found that patients with damage in the right VLPFC made more AS errors compared with patients with left VLPFC lesions (Hodgson et al, 2007). Given that no spatial information was present during the preparatory period, we found bilateral alpha-band modulation in the FEF during the preparatory period in preparation for inhibiting saccades to both hemifields (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Previous animal and human studies have shown that spontaneous and intrinsic fluctuations in alpha-band activity influence stimulus discriminability and performances on motor inhibition (van Dijk et al, 2008;Mazaheri et al, 2009;Haegens et al, 2011;Hamm et al, 2012). As a result, spontaneous rhythmic changes in alpha-band activity have been suggested to reflect intrinsic fluctuations in cortical circuit's efficacy in processing information (Romei et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Data were convolved with a family of modified morlet wavelets from ranging from 2 to 120Hz in 2Hz and 20ms steps with wavelet size increasing linearly from 1 to 20 cycles using code written in MATLAB and EEGLAB 9.0 (Delorme and Makeig, 2004). This approach is ideal for time varying analysis of oscillatory dynamics since it optimizes effective frequency resolution at low frequencies and time resolution at higher frequencies (Hamm et al, 2012). Oscillatory power was expressed in decibels and was averaged over trials.…”
Section: Star Methodsmentioning
confidence: 99%
“…It is calculated by dividing the complex result of the wavelet analysis by its absolute value for every frequency and timepoint (and normalized for number of trials as previously described (Hamm et al, 2012)). Statistical comparisons were carried out in the same manner as for spectral power, except focusing the first 150 ms where the response is maximal.…”
Section: Star Methodsmentioning
confidence: 99%
“…Instead, we focus on a frequency band that has been shown to facilitate spatial attention and enable information transfer between the cerebral hemispheres (43,44): the low-frequency amplitude envelope of α-band activity. The amplitude envelope correlation (AEC) (45) between pairs of MEG sensors can be used to examine whole-brain coordination potentially associated with information transfer.…”
Section: Dynamic Network Constructionmentioning
confidence: 99%